2003
DOI: 10.1116/1.1569926
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of aligned carbon nanotube arrays for electrochemical sensing applications

Abstract: The excellent optoelectronic, mechanical, and thermal properties of carbon nanotubes have made them very attractive for a wide range of potential applications. However, many applications require the growth of aligned carbon nanotubes with surface modification. We have developed a simple pyrolytic method for large-scale production of aligned carbon nanotube arrays perpendicular to the substrate. These aligned carbon nanotube arrays can be transferred onto various substrates of particular interest (e.g., polymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…This resistance value is significantly lower than that of amorphous carbon (> 1 kX/square), which is often formed on top of CNTs during normal CVD based growth processes using inorganic iron(III) compounds. [22] The Fe content of the CL layer was measured to be <5 % using energy dispersive X-ray analysis (EDXA, data not shown) and thermogravimetric analysis (TGA, Fig. S3).…”
mentioning
confidence: 99%
“…This resistance value is significantly lower than that of amorphous carbon (> 1 kX/square), which is often formed on top of CNTs during normal CVD based growth processes using inorganic iron(III) compounds. [22] The Fe content of the CL layer was measured to be <5 % using energy dispersive X-ray analysis (EDXA, data not shown) and thermogravimetric analysis (TGA, Fig. S3).…”
mentioning
confidence: 99%
“…The effect of the gasification depends on the type of reactant used [24]. The first growth of high quality single wall nanotubes was achieved by Smalley and coworkers [25].…”
Section: Laser Ablation Methodsmentioning
confidence: 98%
“…Their small size with larger surface; high sensitivity, fast response and good reversibility at room temperature enable them as a gas molecule sensor [61]; enhanced electron transfer when used as electrodes in electrochemical reactions [62]; and easy protein immobilization with retention of activity as potential biosensors [62] are among some of the desirable applications. Studies have shown that surface modification performed on aligned carbon nanotubes even furthers the sensitivity of nanotube sensors [25]. The main advantage of these sensors are the nanscopic size of the nanotube sensing element and the corresponding nanoscopic size of the material required for a response [50].…”
Section: Sensors and Probesmentioning
confidence: 99%
“…Another example is the synthesis of conducting coaxial nanowires, useful for optoelectronic and sensing applications. Aligned carbon nanotubes were coated uniformly by electrochemical deposition with an appropriate conducting polymer [126127]. …”
Section: Reviewmentioning
confidence: 99%